(untitled) (Computer systems and information technologies, 2023)
Recently, software has been intensively used in almost all areas of business. Testing is an integral process of the software life cycle, during which it is proved that the software meets the specified requirements and needs of the customer, thereby ensuring the quality of the software. The article analyses the tools for software testing with their generalisation by levels of testing. The study has shown that there are a number of studies aimed at reviewing and classifying software testing tools. The correct choice of software testing tools is one of the vital elements to ensure the quality of the entire project. However, most studies in the field of testing focus on describing testing methods without directly connecting to the tools that are based on these methods. A specialist’s approach to software testing requires additional information about the testing tools currently available. With the increasing complexity of software products and shorter development cycles, it is clear that manual testing cannot deliver the level of quality required by the market. Choosing the wrong testing tools for a project leads to inadequate quality measurements or tool changes during the project. Both wrong choice and change of testing tools during the development process affect the quality of the software product and, as a result, the success of the project as a whole. The classifiers discussed in this paper can be used to select software testing tools appropriately. On the one hand, it can be useful for navigating a wide range of testing subjects, reducing the time required for specialists to find the right solution. On the other hand, it can be used as a short introduction to the rapidly developing field of testing and available testing tools for those who are not experts in this field. The classification can be applied to testing various software projects, depending on the type of software and development methodology.